2016
DOI: 10.1002/15-1100
|View full text |Cite
|
Sign up to set email alerts
|

Forest restoration treatments have subtle long‐term effects on soil C and N cycling in mixed conifer forests

Abstract: Decades of fire suppression following extensive timber harvesting have left much of the forest in the intermountain western United States exceedingly dense, and forest restoration techniques (i.e., thinning and prescribed fire) are increasingly being used in an attempt to mitigate the effects of severe wildfire, to enhance tree growth and regeneration, and to stimulate soil nutrient cycling. While many of the short-term effects of forest restoration have been established, the long-term effects on soil biogeoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 96 publications
(168 reference statements)
3
13
0
Order By: Relevance
“…Banning et al () found that thinning affected soil N cycling up to at least 2 years post‐treatment, by increasing the potential for nitrification, particularly when combined with prescription burning for rehabilitated post‐mining forests in Western Australia. Furthermore, our results align well with numerous studies reporting inconclusive or net losses in soil macronutrients following single and multiple prescribed burns in fire‐prone grassy woodlands of Australia (Prober et al ; Burrows et al ), Allepo pine ( Pinus halepensis ) shrublands of Spain (Outeiro et al ), and following tree thinning and prescribed burning in other fire adapted ecosystems of North America (Knoepp et al ; Boerner & Brinkman ; Trammell et al ; Grady & Hart ; Ganzlin et al ).…”
Section: Discussionsupporting
confidence: 90%
“…Banning et al () found that thinning affected soil N cycling up to at least 2 years post‐treatment, by increasing the potential for nitrification, particularly when combined with prescription burning for rehabilitated post‐mining forests in Western Australia. Furthermore, our results align well with numerous studies reporting inconclusive or net losses in soil macronutrients following single and multiple prescribed burns in fire‐prone grassy woodlands of Australia (Prober et al ; Burrows et al ), Allepo pine ( Pinus halepensis ) shrublands of Spain (Outeiro et al ), and following tree thinning and prescribed burning in other fire adapted ecosystems of North America (Knoepp et al ; Boerner & Brinkman ; Trammell et al ; Grady & Hart ; Ganzlin et al ).…”
Section: Discussionsupporting
confidence: 90%
“…This is different from the findings of Hu et al [54], who reported that soil P in reforested spruce forests was not affected by thinning in the first four years, but this is consistent with previous studies that found that the time period since the application of thinning seemed to significantly affect soil P [55] and that the extractable P content declined over 30 years post-thinning [52]. The possible reason for such a difference is that soil nutrients are related to the composition and growth of aboveground species [22,37], and thinning could increase the uptake of P by plants [52,56,57]. Larch is a fast-growing tree species, especially during the middle-age period (21-30 years).…”
Section: Temporal Effects Of Thinning On Light Availability and Soil supporting
confidence: 84%
“…In the larch plantations of this study, the temporal effects of thinning on the soil C concentrations were not significant (Figure 4), which was inconsistent with the first hypothesis and previous studies. Several studies have found that the short-term (1-3 years after thinning) effect increased the total mineral soil C concentrations [50], but the medium-term (5 and 7 years) or long-term (11 years) effects had no significant influence on soil C [22,37]. These results in part suggest that the thinning effects may persist only for a short term.…”
Section: Temporal Effects Of Thinning On Light Availability and Soil mentioning
confidence: 96%
See 1 more Smart Citation
“…), reduce fuel loads, increase general forest productivity and to enhance plant and animal diversity (Gaines and Creed , Ganzlin et al. ). Using fire as a management strategy has the propensity to alter soil organic matter (SOM) and microbial populations.…”
Section: Introductionmentioning
confidence: 99%